Production of arabitol from glycerol by immobilized cells of Wickerhamomyces anomalus WC 1501 - Ranieri, Raffaella; Candeliere, Francesco; Sola, Laura; Leonardi, Alan; Rossi, Maddalena; Amaretti, Alberto; Raimondi, Stefano (Frontiers in Bioengineering and Biotechnology, 2024)
Polyalcohols such as arabitol are among the main targets of biorefineries aiming to upcycle wastes and cheap substrates. In previous works Wickerhamomyces anomalus WC 1501 emerged as an excellent arabitol producer utilizing glycerol. Arabitol production by this strain is not growth associated, therefore, in this study, pre-grown cells were entrapped in calcium alginate beads (AB) and utilized for glycerol transformation to arabitol. Flasks experiments aimed to assess the medium composition (i.e., the concentration of inorganic and organic nitrogen sources and phosphates) and to establish the appropriate carrier-to-medium proportion. In flasks, under the best conditions of ammonium limitation and the carrier:medium ratio of 1:3 (w/v), 82.7 g/L glycerol were consumed in 168 h, yielding 31.2 g/L arabitol, with a conversion of 38% and volumetric productivity of 186 mg/mL/h. The process with immobilized cells was transferred to laboratory scale bioreactors with different configurations: stirred tank (STR), packed bed (PBR), fluidized bed (FBR), and airlift (ALR) bioreactors. The STR experienced oxygen limitation due to the need to maintain low stirring to preserve AB integrity and performed worse than flasks. Limitations in diffusion and mass transfer of oxygen and/or nutrients characterized also the PBR and the FBR and were partially relieved only in ALR, where 89.4 g/L glycerol were consumed in 168 h, yielding 38.1 g/L arabitol, with a conversion of 42% and volumetric productivity of 227 mg/mL/h. When the ALR was supplied with successive pulses of concentrated glycerol to replenish the glycerol as it was being consumed, 117 g/L arabitol were generated in 500 h, consuming a total of 285 g/L glycerol, with a 41% and 234 mg/L/h. The study strongly supports the potential of W. anomalus WC 1501 for efficient glycerol-to-arabitol conversion using immobilized cells. While the yeast shows promise by remaining viable and active for extended periods, further optimization is required, especially regarding mixing and oxygenation. Improving the stability of the immobilization process is also crucial for reusing pre-grown cells in multiple cycles, reducing dead times, biomass production costs, and enhancing the economic feasibility of the process.